Eksplorasi Konsep Sabar dan Syukur dalam Ketahanan Ekonomi Islam - Achmad Muchson Tohari (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2025)
Islamic economic resilience is not solely built upon financial systems and policy instruments, but also upon the strength of Islamic spiritual values that shape economic behavior within the Muslim community. Among these values, sabr (patience) and shukr (gratitude) hold significant conceptual and normative potential in establishing a framework for economic resilience grounded in maqashid sharia. This study aims to explore in depth the meanings of sabr and shukr in Islam and analyze their relevance to the construction of Islamic economic resilience. Employing a qualitative approach through conceptual literature analysis, this study utilizes an integrative literature review method and thematic content analysis of both classical (turath) and contemporary sources, including journal articles. The findings reveal that sabr functions as a psycho-spiritual mechanism to endure economic pressure, while shukr fosters a consciousness of abundance and balanced consumption. Both values are intrinsically linked to the objectives of Islamic law and can be articulated as foundational elements in building holistic, just, and spiritually rooted economic resilience. The principal contribution of this article lies in the development of a new conceptual framework that positions sabr and shukr as strategic components in strengthening Islamic economic systems. This implies that integrating spiritual values into Islamic economic practice offers a viable alternative approach for fostering economic resilience that transcends material dimensions, aligns with Islamic ethical principles, and responds effectively to contemporary economic challenges.